1982
DOI: 10.3386/w0968
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Accelerator Model of R&D and Physical Investment

Abstract: The authors are particularly indebted to Zvi Griliches for his interest and suggestions, and they have benefited from reading Uri Ben-Zion's and Ariel Pakes's related studies (in this volume) and from helpful discussions with them and with John Bound. The authors also thank Edmond Malinvaud, Alain Monfort, and Pascal Mazodier for their comments on a preliminary draft. This work is an outgrowth of a larger National Bureau of Economic Research project on R&D and Productivity supported by the National Science Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…The sample variance in the growth rate of investment is four times as large as the variance in the growth rate of R&D. For only seven of the 191 firms is the ranking of these variances reversed. This conclusion also holds for the (log) levels and has been observed in other samples (see Mairesse and Siu (1984)). Since R&D moves more smoothly over time than investment, the neoclassical model of investment is compelled to rationalize this empirical fact by finding that R&D is subject to more severe costs of adjustment than capital investment.…”
supporting
confidence: 82%
“…The sample variance in the growth rate of investment is four times as large as the variance in the growth rate of R&D. For only seven of the 191 firms is the ranking of these variances reversed. This conclusion also holds for the (log) levels and has been observed in other samples (see Mairesse and Siu (1984)). Since R&D moves more smoothly over time than investment, the neoclassical model of investment is compelled to rationalize this empirical fact by finding that R&D is subject to more severe costs of adjustment than capital investment.…”
supporting
confidence: 82%
“…
It is known that innovations in the market value of manufacturing firms and their R&D expenditures are related (Pakes 1985, Mairesse andSiu 1984). This could be due to shifts in the demand for the output of a particular firm, to shifts in the technological opportunities available to the firm, or to both.
…”
mentioning
confidence: 98%
“…Specifically, Chiao (2001), who studied the short run and long run connection between a firm"s R&D investment and the firm"s financial outcome, pointed out that the long run correlation between a firm"s R&D investment and financial performance was positive while the short run relationship is bi-directional. Mairesse and Siu (1984) also carried on a study that revealed no short run connection between a firm"s R&D expense and financial performance. Thus, in our study, we will examine the relationship between a firm"s previous year"s R&D expenditure as an instrumental variable and the firm"s current year financial performance by using the 1-year lagged value of R&D expense to examine the long term effect of research and development activities on a firm"s financial performance.…”
Section: Research and Developmentmentioning
confidence: 99%